2005
DOI: 10.1002/ajmg.a.30980
|View full text |Cite
|
Sign up to set email alerts
|

A novel DFNA9 mutation in the vWFA2 domain of COCH alters a conserved cysteine residue and intrachain disulfide bond formation resulting in progressive hearing loss and site‐specific vestibular and central oculomotor dysfunction

Abstract: Mutations within the COCH gene (encoding the cochlin protein) lead to auditory and vestibular impairment in the DFNA9 disorder. In this study, we describe the genetic mapping of progressive autosomal dominant sensorineural hearing loss first affecting high-frequency auditory thresholds within a human pedigree to the long arm of chromosome 14 in band q12. A maximal pairwise LOD score of 7.08 was obtained with marker D14S1021. We identified a c.1625G > T mutation in exon 12 of COCH that co-segregates with audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 34 publications
(42 reference statements)
4
67
2
Order By: Relevance
“…The FCH domain is the site of at least seven known mutations in COCH gene (Usami et al, 2003;Nagy et al, 2004;Street et al, 2005;Robertson et al, 2006), all located within exons 4 or 5. These mutations were observed in patients carrying the diagnosis of DFNA9 (Grabski et al, 2003;Robertson et al, 2006), Meniere's disease and presbyacusis (Fransen et al, 1999).…”
Section: The Fch (Or Lccl) Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…The FCH domain is the site of at least seven known mutations in COCH gene (Usami et al, 2003;Nagy et al, 2004;Street et al, 2005;Robertson et al, 2006), all located within exons 4 or 5. These mutations were observed in patients carrying the diagnosis of DFNA9 (Grabski et al, 2003;Robertson et al, 2006), Meniere's disease and presbyacusis (Fransen et al, 1999).…”
Section: The Fch (Or Lccl) Domainmentioning
confidence: 99%
“…Abnormal central oculomotor functions have been reported in family members with the c.1625G > T COCH alteration implying a possible central nervous system change due to cochlin mutation (Street et al, 2005). Geographical distribution of patients, lack of comprehensive medical record and other regulatory statues have prohibited an efficient retrospective study to assess the frequency and severity of glaucoma in DFNA9 patients.…”
Section: Glaucoma and Progressive Hearing Lossmentioning
confidence: 99%
“…Including the novel G87W mutation, nine different mutations have been identified, of which eight occur in the LCCL domain (V66G, W117R, G88E, P51S, I109N, A119T, V104del, G87W [Collin et al, 2006;de Kok et al, 1999;Kamarinos et al, 2001;Nagy et al, 2004;Robertson et al, 1998;Usami et al, 2003]). A recent study reported on the first DFNA9 mutation in the vWFA2 domain (C542F) [Street et al, 2005]. Liepinsh and colleagues showed that, except for W117R, all the other then-known mutations (P51S, V66G, G88E, I109N, W117R) in the LCCL domain disrupt its normal structure and lead to protein misfolding of this domain [Liepinsh et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…COCH was chosen as a candidate for hearing loss due to its high expression in the Morton fetal cochlear cDNA library (Robertson et al, 1994;Robertson et al, 1997). Mutations in the gene have since been found to be responsible for DFNA9 in a number of families around the world (Robertson et al, 1998;de Kok et al, 1999;Fransen et al, 1999;Kamarinos et al, 2001;Usami et al, 2003;Nagy et al, 2004;Kemperman et al, 2005;Street et al, 2005;Collin et al, 2006;Pauw et al, 2007). But, although this relationship is well-established, mice deficient in Coch do not exhibit hearing loss (Makishima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%